Charles-Joseph Hubert et la lecture rhétorique - Goyet, Francis (Rivista Italiana di Filosofia del Linguaggio, 1970)
The reading of great orators was an important part of the rhetorical classes. Still, it is essential to describe this rhetorical lecture, in order to avoid to anachronically identify it to our modern practice of reading great authors in classrooms. The first part of my article will be dedicated to this question, basing my development on Charles-Joseph Hubert’s 1839 reflexion and his formula on “le bréviaire des rhétoriciens”. This testimony illustrates the kind of reconstitution of the rhetorical class practiced by the RARE (Rhétorique de l’Antiquité à la Révolution) team from 1998. This will be the second part of the article.